2021
DOI: 10.1108/oir-08-2020-0374
|View full text |Cite
|
Sign up to set email alerts
|

Why people spread rumors on social media: developing and validating a multi-attribute model of online rumor dissemination

Abstract: PurposeDealing with online rumors or fake information on social media is growing in importance. Most academic research on online rumors has approached the issue from a quantitative modeling perspective. Less attention has been paid to the psychological mechanisms accounting for online rumor transmission behavior on the individual level. Drawing from the theory of stimulus–organism–response, this study aims to explore the nature of online rumors and investigate how the informational characteristics of online ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Various motivations—romantic, information seeking, attention seeking (status attainment), entertainment, relation enhancement, self-enhancement, and socializing—have been identified (Lee and Ma, 2012; Goh et al. , 2009; Shen et al. , 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Various motivations—romantic, information seeking, attention seeking (status attainment), entertainment, relation enhancement, self-enhancement, and socializing—have been identified (Lee and Ma, 2012; Goh et al. , 2009; Shen et al. , 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Several studies have referred to the uses and gratifications theory to interpret social media-based information-sharing behavior (Thompson et al, 2020). Various motivationsromantic, information seeking, attention seeking (status attainment), entertainment, relation enhancement, self-enhancement, and socializing-have been identified (Lee and Ma, 2012;Goh et al, 2009;Shen et al, 2021). Talwar et al (2019) showed that social media fatigue, social comparison, self-disclosure, fear of missing out, and online trust influence fake news sharing intention.…”
Section: Covid-19related Fake Newsmentioning
confidence: 99%
“…In fact, OSNs have been exploited for spreading fake news and rumors (Zubiaga et al. , 2018; Shelke and Attar, 2019; Shen et al. , 2021).…”
Section: Bunet Dataset Utilitymentioning
confidence: 99%
“…The study of information diffusion (Kim et al, 2018;Bhowmick, 2020;Kumar et al, 2021) has been investigated more on intra than on inter-social networks as it is easy to identify connections used to transport data on intra-social networks. In fact, OSNs have been exploited for spreading fake news and rumors (Zubiaga et al, 2018;Shelke and Attar, 2019;Shen et al, 2021). Zubiaga et al (2018) focused on the detection of the spread of false information on one social network but it seems that there is just few works OIR 47,1 (Farahbakhsh et al, 2016;Keikha et al, 2020) tackling the spread of information across multiple OSNs, due to the lack of cross-social networks datasets.…”
Section: Cross-network Information Spreadmentioning
confidence: 99%
“…The flexibility and simplicity with which information on social media platforms may be disseminated stimulate the spread of information across the network, regardless of its veracity. This sort of disinformation is typically disseminated in the event of an exclusive piece of news [34,35]. As a result of unconfirmed information, such information, sometimes referred to as rumors, has the potential to do catastrophic damage.…”
Section: Introductionmentioning
confidence: 99%